DAMPAK PENGELOLAAN SAMPAH PADAT TERHADAP KUALITAS AIR PANTAI BATAKAN, TANAH LAUT KALIMANTAN SELATAN - Habudin Habudin; Fatmawati Fatmawati; Emmy Sri Mahreda; Herliwat Herliwati (Universitas Lambung Mangkurat, 2022)
Batakan Village, Panyipatan District, Tanah Laut Regency is one of the villages in South Kalimantan, which in addition to having natural tourism potential is also a fishing village. This study aims to analyze the impact of solid waste management on batakan beach water quality. Sampling at the location is taken by means of instantaneous sampling (grab sample). A misguided sample or grab sample is a sample taken directly from a body of water that is on the beach. The water quality sampling procedure uses the surface water sampling method in accordance with SNI 6989.57:2008, at the sampling point locations that have been determined purposively. Research parameters in the form of physics, namely temperature and brightness. Chemistry in the form of pH, Do, salinity, TSS, COD and BOD. Based on the results of water quality measurements obtained several parameters that meet the water quality standards for marine biota, namely the research parameters in the form of physics, namely temperature and brightness. Chemistry in the form of pH, DO, salinity, COD and BOD. Meanwhile, TSS does not meet the standards of the Decree of the State Minister of the Environment No. 51 in 2004.